Delivering Integrated Pest and Pollinator Management (IPPM). (June 2020) - Egan, Paul A.; Dicks, Lynn V.; Hokkanen, Heikki M.T.; Stenberg, Johan A.
Abstract : The need to reduce pollinator exposure to harmful pesticides has led to calls to expedite the adoption of integrated pest management (IPM). We make the case that IPM is not explicitly 'pollinator friendly', but rather must be adapted to reduce impacts on pollinators and to facilitate synergies between crop pollination and pest control practices and ecosystem services. To reconcile these diverse needs, we introduce a systematic framework for 'integrated pest and pollinator management' (IPPM). We also highlight novel tools to unify monitoring and economic decision-making processes for IPPM and outline key policy actions and knowledge gaps. We propose that IPPM is needed to promote more coordinated, ecosystem-based strategies for sustainable food production, against the backdrop of increasing pesticide regulation and pollinator dependency in agriculture. Video Abstract: Highlights: Integrated pest management (IPM) has been promoted as a response to mitigate pollinator decline, yet IPM itself is not explicitly 'pollinator friendly'. IPM strategies require adapting to reconcile crop pollination trade-offs and to the harmonise the delivery of pollination and pest regulation practices and ecosystem services. A systematic framework for 'integrated pest and pollinator management' (IPPM) is proposed to enhance IPM compatibility with crop pollination management and is underpinned by a novel approach to unify economic decision making. Highlighted policy actions and cutting-edge support tools can assist the design and implementation of IPPM strategies.